Analytical application of functionalized CdS and ZnS as fluorescence label for the determination of proteins - Ramasundram, Shemalah (2005)
The quantitative analysis of protein is essential in biochemistry and clinical medicine. The most sensitive quantitation of protein at this present is generally based on fluorescence enhancement on organic dyes determination. However, this organic fluorophores often suffer from photobleaching and low signal intensity. In order to overcome such problems, the study was carried out to investigate the possibility of employing the luminescent particle functionalized CdS and ZnS for quantitative analysis of protein. CdS have been prepared and capped with mercaptoacetic acid (functionalized CdS) whereas ZnS was capped with cysteine (functionalized ZnS), which renders the particles water soluble and biocompatible. Fluorescence studies showed at excitation wavelength exc = 233 nm, the maximum emission wavelength of functionalized CdS was at 350 nm whereas for functionalized ZnS was at 357 nm wavelength. Further, general optimization procedure such as the effect of pH, temperature, concentration, reaction time of the functionalized CdS and functionalized ZnS binding with BSA (Bovine Serum Albumin) was conducted. A positive correlation with R2 = 0.9899 was obtained between CdS capped with mercaptoacetic acid binding with BSA meanwhile correlation between ZnS capped cysteine and BSA was 0.9805. The interferences of various metal ions and surfactant were subsequently performed in order to obtain the selectivity of the developed assay on the determination of BSA. The effect of surfactant such as ionic detergent sodium dodecyl sulfate (SDS), nonionic detergent Triton X-100 shows signification shift towards a shorter wavelength. Limit of detection for functionalized CdS binding with BSA was 0.14 ppm followed by limit of detection of functionalized ZnS binding with BSA was 0.09 ppm. This developed method was successfully applied to the several types of protein such as egg albumin, lysozyme and amylase. The developed novel assay is simple, inexpensive, rapid and sensitive